2014
DOI: 10.1104/pp.114.244814
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of the Cytochrome P450 CYP76 Family from Arabidopsis thaliana in the Metabolism of Monoterpenols and Phenylurea Herbicides

Abstract: Comparative genomics analysis unravels lineage-specific bursts of gene duplications related to the emergence of specialized pathways. The CYP76C subfamily of cytochrome P450 enzymes is specific to Brassicaceae. Two of its members were recently associated with monoterpenol metabolism. This prompted us to investigate the CYP76C subfamily genetic and functional diversification. Our study revealed high rates of CYP76C gene duplication and loss in Brassicaceae, suggesting the association of the CYP76C subfamily wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 58 publications
2
127
0
Order By: Relevance
“…The levels of 8-OH-linalool and 9-OH-linalool, also formed by the CYP76C2 and CYP76C3 enzymes Höfer et al, 2014), were moderately reduced in the cyp76c1 flowers compared with the wild type, but almost completely abolished in the complemented/35S:CYP76C1 line. The levels of lilac aldehydes and alcohols conjugates were strongly reduced in the cyp76c1 flowers and partially restored in the complemented/35S: CYP76C1 line.…”
Section: A Major Proportion Of the Cyp76c1-derived Linalool Oxides Ismentioning
confidence: 94%
See 3 more Smart Citations
“…The levels of 8-OH-linalool and 9-OH-linalool, also formed by the CYP76C2 and CYP76C3 enzymes Höfer et al, 2014), were moderately reduced in the cyp76c1 flowers compared with the wild type, but almost completely abolished in the complemented/35S:CYP76C1 line. The levels of lilac aldehydes and alcohols conjugates were strongly reduced in the cyp76c1 flowers and partially restored in the complemented/35S: CYP76C1 line.…”
Section: A Major Proportion Of the Cyp76c1-derived Linalool Oxides Ismentioning
confidence: 94%
“…This study also suggested the presence of partially redundant P450 enzymes that may contribute to floral linalool metabolism. The hypothesis of the involvement of other P450 oxygenases in floral linalool metabolism was then further supported by a systematic functional exploration of the expression patterns and in vitro activities of the CYP76C3 paralogs present in Arabidopsis (Höfer et al, 2014), which revealed floral expression of CYP76C2 and CYP76C1, two other monoterpenol-metabolizing oxygenases. CYP76C1 emerged as the best candidate due to its high and selective linalool oxygenase activity, which is 10 times higher than the activity of CYP76C2.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…10-Hydroxygeraniol is an important precursor for the biosynthesis of (seco) iridoids, which are pharmaceutically important compounds and include the anticancer agents vincristine and vinblastine (O'Connor and Maresh 2006). Cytochrome P450 enzymes, especially CYP76 family members such as CYP76B6 from Catharanthus roseus and CYP76C1 from Arabidopsis thaliana, were reported to catalyze the hydroxylation of geraniol (Collu et al 2001;Hofer et al 2014;Hofer et al 2013).…”
Section: Introductionmentioning
confidence: 99%